Awareness regarding the strategies to bring down the pandemic among general population: a questionnaire based study - Balaji, Varsha Christy Rani; R., Nithya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The behavior of the general public will likely have an important effect on how the coronavirus disease 2019 (COVID-19) epidemic spreads, especially when the first wave is diminishing. The aim of the study is to determine the awareness regarding the strategies to bring down the pandemic among the general population of Tamil Nadu in South India. Methods: A cross-sectional online survey conducted in October 2020. A sample of consenting 500 adult, healthy caregivers of patients attending a tertiary medical institute who were representative of the general population formed the study group. They filled a pre-formed questionnaire. All data entry and analysis were performed using SPSS (version 24). Descriptive statistics and chi-square test were performed between the various sociodemographic factors of age, gender, occupation, and education, and COVID-19 exposure in the family. P≤0.05 was taken to be significant. Results: It was observed that age had a significant influence on the wearing of masks and the use of hand sanitizer. Gender, age and education are the important determinants for use of hand sanitizer, wearing a mask, practicing social distancing, avoid traveling to the infected areas as well as washing hands often and always using a facemask to prevent COVID-19 were statistically significant. Conclusions: The dynamics of the impact of the awareness campaign and public participation are understood by the results. There is a need for a training program with respect to locale-specific scenario targeted to a specific cluster of population emplaning upon their respective lifestyle, to improve the knowledge and compliance about risk and preventions.